Men and women enjoying the difference - Crabb, Larry (Grand Rapids, MI Zondervan, 1991)
Includes bibliographical references.
Donated by Pieter Dijkstal, 5/2003.
Keywords: Marriage counselling -- religious aspects -- Christianity; Married people